Elementary school students' attitudes towards peers with disabilities: The role of personal and contextual factors. Issue 1 (2nd January 2022) - Di Maggio, Ilaria; Ginevra, Maria Cristina; Santilli, Sara; Nota, Laura
ABSTRACT: Background: Attitudes of classmates has been considered as one of the major problems in inclusive education, negatively influencing the participation of students with disability in school contexts. The goal of this study was to examine Italian typically developing children's attitudes towards their peers with disabilities. Method: In a sample of 560 elementary school students aged 6 - 11 years old we tested - through multiple regression analysis - the impact of personal and contextual factors, such as sex and age of participants, type of disability of peers with disabilities, experience with peers with disabilities and, in particular, the type of presentation of students with disabilities on attitudes of elementary school students without disability. Results: Results showed that girls and younger students generally hold more positive attitudes towards peers with disabilities. Less accepting attitudes towards peers with behaviour problems than those with intellectual or sensory disabilities were also found. Experience with peers with disabilities in class was not related to attitudes towards disabilities; instead, providing a positive presentation of peers with disabilities associated with their strengths positively impacted attitudes towards disabilities, regardless of sex and age of participants and type of disability of peers. Conclusions: The results of our study suggested the impact of the type of information provided to students about disabilities on their attitudes. Particular emphasis should be given to the way in which children with disabilities are presented to typically developing classmates, and information provided should stimulate a positive image of peers with disabilities.